2015
DOI: 10.1523/jneurosci.1068-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Parietal Reach Region Affects Reaching But Not Saccade Choices in Internally Guided Decisions

Abstract: The posterior parietal cortex (PPC) has traditionally been considered important for awareness, spatial perception, and attention. However, recent findings provide evidence that the PPC also encodes information important for making decisions. These findings have initiated a running argument of whether the PPC is critically involved in decision making. To examine this issue, we reversibly inactivated the parietal reach region (PRR), the area of the PPC that is specialized for reaching movements, while two monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 50 publications
(6 reference statements)
5
38
1
Order By: Relevance
“…Desirability provides a more general measurement to evaluate an alternative, since it includes information not only about the goal itself, but also the action required to achieve that goal. Our theory is inline with a series of neurophysiological and pharmacological intervention studies in animals reporting that areas in the posterior parietal cortex integrate value information to estimate the relative desirability of available options [3034]. On the contrary, although neurons in specific PPC regions exhibit activity patterns that directly resemble the evidence accumulation process posited in race models [35, 36], recent studies reported that silencing these neurons does not influence the decision process [37, 38].…”
Section: Discussionsupporting
confidence: 60%
“…Desirability provides a more general measurement to evaluate an alternative, since it includes information not only about the goal itself, but also the action required to achieve that goal. Our theory is inline with a series of neurophysiological and pharmacological intervention studies in animals reporting that areas in the posterior parietal cortex integrate value information to estimate the relative desirability of available options [3034]. On the contrary, although neurons in specific PPC regions exhibit activity patterns that directly resemble the evidence accumulation process posited in race models [35, 36], recent studies reported that silencing these neurons does not influence the decision process [37, 38].…”
Section: Discussionsupporting
confidence: 60%
“…Reversible inactivation of PRR produces reach specific deficits and LIP a bias toward saccade deficits (Christopoulos et al, 2015; Kubanek and Snyder, 2015; Yttri et al, 2014). A grasp specific deficit has been reported for AIP (Gallese et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Areas within monkey superior parietal (Caminiti et al, 1996;Scherberger et al, 2005) and dorsal premotor Hoshi and Tanji, 2004) cortices are necessary for the transformation of visual information to motor commands for reaching, and critically, the neural responses within these areas also reflect reach choices (Cisek and Kalaska, 2005;Scherberger and Andersen, 2007;Pesaran et al, 2008;Pastor-Bernier and Cisek, 2011;Thura and Cisek, 2014). Temporary inactivation of the "parietal reach region"area PRR, located within the medial bank of the intraparietal sulcusimpairs reach (but not saccade) selection (Christopoulos et al, 2015b). These data provide powerful evidence for the causal involvement of the PPC in reach choices.…”
Section: The Ppic Modelmentioning
confidence: 74%
“…Further, although these studies tend to investigate reach choices involving the same effector, recent data suggest that similar "action-based" competitive models can explain effector-selection (Christopoulos et al, 2015a). Temporary inactivation of reach- (Christopoulos et al, 2015b) versus saccade-selective (Christopoulos et al, 2018) areas in monkey posterior parietal cortex (areas PRR, mentioned above, and the lateral intraparietal area, LIP, respectively) selectively impairs reach versus saccade choices, respectively, and these data can be explained by a computational model that specifies competitive interactions between these brain areas (Christopoulos et al, 2015a). Conceptually, our PPIC model is consistent with this framework.…”
Section: The Ppic Modelmentioning
confidence: 99%